DIAGNOSTIC ACCURACY OF MAGNETIC RESONANCE IMAGING IN MENISCAL INJURIES OF KNEE JOINT AND ITS ROLE IN SELECTION OF PATIENTS FOR ARTHROSCOPY - Rahman, Asif; Nafees, Muhammad; Akram, Muhammad Hamid; Andrabi, Atif Hussain; Zahid, Muhammad (Journal of Ayub Medical College Abbottabad, 2010)
Background: Magnetic Resonance Imaging (MRI) is frequently advised to evaluate clinically suspected cases of meniscal injuries in our setup. The objective was to determine the diagnostic accuracy of MRI in meniscal injuries of knee joint and its effectiveness in selection of patients for arthroscopy. Methods: A Cross-sectional comparative study was conducted at Radiology Department Military Hospital (MH) Rawalpindi in collaboration with Orthopaedic Department Combined Military Hospital (CMH) Rawalpindi from 31 Jan 2007 to 1 Aug 2007. Fifty-seven patients with clinical suspicion of meniscal injuries were subjected to MRI. Arthroscopy was done only in 34 patients while 23 were excluded on the basis of MRI findings. MRI findings were compared with arthroscopic findings. Medial and lateral menisci were considered separately in each case. Results: Among 57 patients only 30 showed significant tear on MRI. Arthroscopy was done in these cases. Arthroscopy was considered on clinical grounds only in 4 patients who did not show significant tear on MRI. MRI showed Medial Meniscus (MM) injury in 23 patients and Lateral Meniscus (LM) injury in 10 patients. Arthroscopy confirmed MM injury in 17 patients and LM injury in 7 patients. MRI missed two MM and one LM injuries. This showed that MRI has sensitivity of 89.4% and specificity of 62% in diagnosing injuries of MM, while sensitivity of 87% and specificity of 88% in diagnosing injuries of LM. Diagnostic accuracy of MRI in MM and LM injuries was 76.4% and 88.2% respectively. Conclusion: MRI is accurate in diagnosing meniscal injuries of knee joint and is effective in selection of patients for arthroscopy. Keywords: Magnetic Resonance Imaging, Meniscal injuries, Arthroscopy